Aktivitas Antibakteri Plum (Prunus domestica L.) - Joana Sirooj Irsyaadyah (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Infectious diseases are a major health problem because the main causes are higher morbidity and mortality rates dominant in developing countries. Management of infectious diseases by giving antibiotics. If it was given irrationally, it can lead to resistance, Therefore an alternative treatment is needed by using plants that have antimicrobial composition reserves. One of the plants that can be antibacterial is a plum fruit. The fruit contains secondary metabolites containing flavonoids, saponins, alkaloids. Flavonoid compounds which are able to denature bacteria can cause cell wall damage. And the composition of saponins can increase cell wall permeability. Plum showed a zone of inhibition against some pathogenic bacteria including Staphylococcus epidermidis followed by Staphylococcus aureus and Proteus mirabilis.